Creditless Recovery in Eastern Europe - Dan Olteanu (Romanian Academy, National Institute for Economic Research, 2014)
This paper aims to investigate the presence of a creditless economic recovery in Eastern Europe, after de 2008-2009 output collapse. To this end, we use three variables: credit stock, credit flow and money supply M1. We find that the changes in the credit flow, as percentage of GDP, are the most distinctly correlated with the GDP rate. During the growth recovery, the credit flow tends to rise in six of the surveyed countries, although the credit stock declines in some cases. On the other side, the liquid segment of money supply (M1) registered in some countries strong rebounds that boosted demand recovery, due not so much to credit but to the liquidity preference. Within domestic demand, we notice a steeper decline of the fixed capital formation than the consumption one, but also a stronger subsequent upturn. The investment recovery seems to be supported in most of countries by the credit flow growth; there is a stronger dependence of capital formation on the newly created credit than in the case of consumption, which is rather correlated with the whole money supply M1. In conclusion, we can say that there was a creditless recovery phenomenon in Eastern Europe after the global crisis, but most countries recorded an increase of credit flow along with the GDP. The new flow of money is mostly used for investment and consumption, and thus supports the revival of domestic demand, especially in countries with a less developed financial system, such as the emerging european ones. On the other hand, the trend in the liquid part of the money supply may evolve, especially in times of financial instability, regardless of credit developments. This, along with other factors, strongly affects the degree to which GDP rely on credit.
Keywords: E44; E51; G01; 330; Credit; Economic Recovery; Phoenix Miracle